Combined effects of gliding-arc plasma and C-phycocyanin on antioxidant activity and shelf-life extension of rainbow trout (Oncorhynchus mykiss) fillets - Maedehsadat Seyedalangi; Amir Hossein Sari; Bahareh Nowruzi; Seyed Amir Ali Anvar (PLoS ONE, 2025)
The study aimed to evaluate the impact of gliding arc plasma (GAP) treatment and phycocyanin pigment (PCP) on the antioxidant activity and refrigerated shelf-life extension of Oncorhynchus mykiss (rainbow trout) fillets (OMR) during 18 days of storage at 4 ± 0.1 °C. The combined treatment of GAP and PCP significantly inhibited microbial growth, with the total viable count in the control sample (C) increasing from 4.39 to 12.08 log CFU/g by day 18, while the combined treatment (P5 + PC) increased only from 3.50 to 9.23 log CFU/g, extending the shelf life from 3 to 12 days. Antioxidant activities (DPPH, ABTS, and FRAP) were markedly higher in treated samples, as DPPH values changed only slightly (from 4.20 to 5.23) compared to the control (from 10.91 to 36.41), and FRAP activity decreased less sharply (35.88 to 25.30 vs. 20.01 to 11.75). Moreover, the total volatile nitrogen (TVN) value in the control rose from 8.77 to 53.95 mg N/100 g, exceeding the international limit (30 mg N/100 g) by day 9, whereas the combined treatment remained below this limit (29.40 mg N/100 g) even on day 18. The n-3/n-6 fatty acid ratio slightly decreased (0.14 to 0.11) but remained within an acceptable nutritional range. Overall, the results indicate that the combined GAP and PCP treatment is an effective and promising approach to extend the shelf life of OMR for more than 12 days under refrigerated conditions while maintaining better antioxidant stability.